2019
DOI: 10.1101/682815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitric oxide acts as a cotransmitter in a subset of dopaminergic neurons to diversify memory dynamics

Abstract: SummaryAnimals employ multiple and distributed neuronal networks with diverse learning rules and synaptic plasticity dynamics to record distinct temporal and statistical information about the world. However, the molecular mechanisms underlying this diversity are poorly understood. The anatomically defined compartments of the insect mushroom body function as parallel units of associative learning, with different learning rates, memory decay dynamics and flexibility (Aso & Rubin 2016). Here we show that nitr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 119 publications
11
53
0
Order By: Relevance
“…We based these divisions on findings that (1) these regions are innervated by different dopaminergic neurons that respond differentially to ‘punishment’ (e.g. electric shock) vs. ‘reward’ (reviewed in Amin and Lin, 2019 ), (2) dopaminergic neurons release synaptic vesicles onto APL in response to electric shocks ( Zhou et al, 2019 ), and (3) APL expresses the dopamine receptors DopEcR ( Aso et al, 2019 ) and the inhibitory Dop2R ( Zhou et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We based these divisions on findings that (1) these regions are innervated by different dopaminergic neurons that respond differentially to ‘punishment’ (e.g. electric shock) vs. ‘reward’ (reviewed in Amin and Lin, 2019 ), (2) dopaminergic neurons release synaptic vesicles onto APL in response to electric shocks ( Zhou et al, 2019 ), and (3) APL expresses the dopamine receptors DopEcR ( Aso et al, 2019 ) and the inhibitory Dop2R ( Zhou et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to reflecting differential synaptic inputs, this spatially localized activity in APL most likely also reflects intrinsic properties of APL’s membrane excitability that prevent activity from spreading. To validate the hypothesis that intrinsic properties could contribute, we analyzed an RNA-seq dataset revealing mRNA levels in the cell bodies of Kenyon cells, dopaminergic neurons, mushroom body output neurons, the dorsal paired medial (DPM) neuron, and APL ( Aso et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, to determine the signs of the connections between identified partners -that is, whether synaptic connections are excitatory or inhibitory-we performed RNA-Seq on each cell type that we could target specifically with Gal4 driver lines ( Figure 2F-H; see Methods) (Aso et al, 2019;Davis et al, 2019). For cell types that did not yield clear answers or that we could not target cleanly, we also used FISH to determine the likely neurotransmitter (Long et al, 2017;Meissner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…What might be the neuronal subsets that produce NO and regulate period length of locomotor activity? A recent study by the group of Y. Aso and G. Rubin [ 54 ], has shown that NO acts as a co-transmitter in a subset of dopaminergic neurons, specifically in some of the PAMs, PPL1s and PPL2abs. It is thus possible that dopamine signaling modulated by NO is involved in the control of the locomotor activity period.…”
Section: Discussionmentioning
confidence: 99%